CULTURAL LIFE OF MOVAROUNNAHR AND KHOREZM IN THE 9TH-12TH CENTURIES - Axmedov Farxodbek Shavkatovich (American Journals, 2023)
This article is prepared on one of the most relevant topics today - "Cultural life of Movarounnahr and Khorezm in the 9th- 12th centuries ". heritage is mentioned.
Keywords: Movarounnahr, spiritual heritage, UNESCO, Asian renaissance, Ma'mun Academy,